A Conceptual Framework of Expert Finding System for Academic Events and Committess - Shirude, Snehalata B; Kolhe, Satish R (International Journal of Computer Sciences and Engineering, 2019)
In academic institutes or universities, there is always a need to find experts in different subjects. The experts are required as resource persons for various workshop, seminars, and conferences. There is always need of experts for working on various research committees. There are various online research groups available on World Wide Web. Many researchers from various domains relate to each other via these online research groups. This paper describes a conceptual framework which finds experts from online research groups for various academic events and committees.